PENGARUH TINGKAT PENDIDIKAN, INVESTASI DAN UPAH MINIMUM TERHADAP KESEMPATAN KERJA DAN IPM KABUPATEN/KOTA PROVINSI BALI - Adi Guna, I Made Prastawa; Yuliarmi, Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Various efforts government to increase growth for the region have a positive impact on welfare, there is still an imbalance of community welfare between regencies / cities in Bali Province. The purpose of this study is to analyze the influence of the level education, investment and minimum wages for employment opportunities and IPM districts / cities in Bali Province. This research is sourced from secondary data. The data collection method is data published by BPS in the Province of Bali. Technique analysis used by path analysis. The results of data analysis obtained the level of education and investment have a positive and significant effect on employment opportunities, while the minimum wage has a positive but not significant effect on employment opportunities. The level of education, investment, minimum wage and employment opportunities has a positive and significant impact on the welfare in Bali Province Regency / City. Employment opportunities partially mediate the effect of education levels on welfare, and employment opportunities partially mediate the effect of investment on welfare, but employment opportunities do not partially mediate the effect of minimum wages on welfare in Bali Regency / City. Keywords: education level, investment, minimum wage, employment opportunity, ipm